Pertanggungjawaban Perusahaan Asuransi Terhadap Pemegang Polis Yang Mengalami Status Polis Lapse (Kehilangan) Akibat Kelalaian Agen Dalam Pembayaran Angsuran Premi (Studi Kasus Putusan No.320/Pdt.G/2019/PN Mdn) - Riska Fitriani Siregar; Muhammmad Citra Ramadhan; Marsella Marsella (ARBITER: Jurnal Ilmiah Magister Hukum, 2022)
In Insurance there is an insurance agreement, explained in the Civil Code: there is an "agreement" which is a condition that must be fulfilled for an agreement to be valid, an insurance agreement will form a legal relationship that is reflected in the agreement, an agreement that regulates terms and obligations, the importance of insurance in its development to advance the development of insurance. Paying premiums is not on time, so the insurance claim submitted is rejected by the company, because it is already in a state of lapse. Not paying is not the insured's fault, but the agent's fault for not depositing the premium to the company. This study aims to determine how agents are arranged in insurance companies in Indonesia and how are insurance companies accountable to customers who experience policy lapse due to agent negligence in paying premiums (Decision No.320.G/2019/PN Mdn). The research method of this thesis was carried out based on reading sources, laws, books, internet, journals, field research, directly conducting research to the Medan District Court with interviews. The results of the study explain that the defendant (PT. Prudential life Assurance) is completely irresponsible and there is no good faith towards the plaintiff (yurnawilis) claiming the insured late. Ambun Sari (the plaintiff's biological mother), the case was also declared obscuur libel (blurred) posita and the plaintiff's petitum are not related, it does not mean that the defendant is not responsible for the insurance claim.